Comparison of methods for quantitating bronchial morphology. Issue 4 (July 1971) - Bedrossian, Carlos W. M.; Anderson, A. E.; Foraker, Alvan G.
Abstract : To determine the relative accuracy and efficiency of certain methods currently being used to assess bronchial architecture, results obtained with the respective techniques were compared with `true' values derived from planimetry on the bronchi of 30 subjects. Excellent comparative figures were obtained for each bronchial constituent measured (gland, cartilage, and bronchial wall areas) with the point count method and weighing paper cut-outs. The latter seemed to be the most economical from the standpoint of time saving. Results of Reid indices, acinar counts, and determinations of percentage mucous acini (applicable only to glandular structures) correlated poorly with planimetry.